A Study on Different Topologies of the Tubular Linear Permanent Magnet Motor Designed for Linear Reciprocating Compressor Applications - Abdalla, Izzeldin I.; Ibrahim, Taib B.; Nor, Nursyarizal M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents a study on three different topologies of tubular linear permanent magnet motors (TLPMMs), with different permanent magnet (PM) structures. These motors provide direct conversion for electrical energy into a linear mechanical force, and they are directly coupled to the load. The proposed motors are equipped with quasi-Halbach magnetized moving-magnet armatures and their stator cores have been made from a soft magnetic composite (SMC) material, Somaloy 700. Based on the nonlinear time-stepping two-dimensional finite-element analysis (2-D FEA) an extensive magnetic field analysis of the proposed designs has been established. The simulation results indicate the effectiveness of the designs to drive a linear reciprocating compressor in a household refrigerator. Moreover, the simulation results have shown that, the superiority of the two designs with T-shaped and trapezoidal-shaped PMs structures over the TLPMM with conventional rectangular-shaped PMs. In addition to that, the usage of quasi-Halbach for the PMs array arrangement has a significant effect on the motor performance.